Aqueous-Core Nanocapsules of Lamivudine: Optimization by Design of Experiments - Srikar, Grandhi (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The prior objective of the current work was to optimize the surfactant concentration and type of polymer to achieve high entrapment efficiency, less particle size, and less drug release rate constant of aqueous core nanocapsules (ACNs) containing lamivudine. Materials and Methods: Modified multiple emulsion technique was used to prepare the nanocapsules with biodegradable polymers, namely, poly (lactide-co-glycolide) and polylactic acid; and the surfactant employed was Span 80. The experiments were designed by one factorial design that was repeated for every categoric factor under response surface methodology of design of experiments using Stat-Ease Design-Expert software. Results: The obtained results of response variable, namely, entrapment efficiency, particle size, and drug release rate constant were statistically treated by ANOVA for response surface quadratic model and found that influence of both factors on all the response variables was significant at P < 0.05. The optimized formulation was found to have the entrapment efficiency of 77.12%, particle size of 250.3 nm, and the drug release rate constant of 0.106 hâˆ’1. Conclusion: The results indicated that the objective of this was achieved and ACNs technique was efficient to develop nanoparticles for water-soluble drugs with improved efficiency.